EFEKTIVITAS PELAKSANAAN SISTEM INFORMASI KESEHATAN ONLINE PADA DINAS KESEHATAN KABUPATEN ROKAN HILIR - Isnaini "; Abdul Sadad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research was conducted to find out the effectiveness of the implementation of online health information systems in health office of Rokan Hilir Regency. The background of this research is health office of Rokan Hilir regency as institutions which develops online health information system and efforts to improve the quality of health services integratedly to the society. The existence of this online health information systems coordination, then the decision making process, the process of handling problems, performance improvement officer health and wellness data can be obtained accurately and realtime. This research aims to know the implementation of the online health information system, factors that affect the provision of online health information systems in health office of Rokan Hilir Regency.The research method is qualitative descriptive with the purposive sampling technique. Informants in this study are the health office of Rokan Hilir Regency, Secretary of health office, Head of sub-division of planning and programs, Staff of sub-division of planning and programs, head of Bagan Punak Clinic, head of Rimbo Melintang clinic.Result of research of qualitative descriptive data analysis, the Data Type is primary data and secondary data collected through observation, interview and documentary studies. The result of this study shows that the implementation of online health information systems in health office of Rokan Hilir Regency is not done properly. This can be seen from bad of the process of data reporting by the health centers that exist in the Rokan Hilir. Restricting factors in the implementation of online health information systems is still plentiful. Restricting Factors that faced include human resources, disruption of networks, facilities and inadequate of infrastructure. This causes the disruption of the drafting process of health profile of Rokan Hilir health office.Keywords : Effectiveness, Organization Effectiveness, Online Health Information Systems.